2013
DOI: 10.3390/ijerph10126422
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Traumatic Dental Injury on the Quality of Life of Brazilian Preschool Children

Abstract: This study aimed to assess the impact of traumatic dental injury (TDI) on the quality of life of preschoolers and their families. A cross-sectional study was carried out, with a sample of 814 children, aged three to five years old, in Campina Grande, Brazil. Parents/caregivers were asked to complete the Brazilian Early Childhood Oral Health Impact Scale and a questionnaire on socio-demographic data. Oral examinations of the children were performed by three previously calibrated dentists. Bivariate and multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 42 publications
4
55
0
1
Order By: Relevance
“…With regard to parents/ caregivers, traumatic dental injury may not have been given importance or even perceived due to the fact that most cases were enamel fractures [Viegas et al, 2012;Siqueira et al, 2013]. For the children, however, traumatic dental injury may have exerted an influence on appearance, as children at this age have perceptions regarding aesthetics [Tsakos et al, 2012], or even pain (in case of a more serious traumatic dental injury).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to parents/ caregivers, traumatic dental injury may not have been given importance or even perceived due to the fact that most cases were enamel fractures [Viegas et al, 2012;Siqueira et al, 2013]. For the children, however, traumatic dental injury may have exerted an influence on appearance, as children at this age have perceptions regarding aesthetics [Tsakos et al, 2012], or even pain (in case of a more serious traumatic dental injury).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, children may have memories of the time of the traumatic dental injury, even in cases of mild injuries. Previous studies that have discarded this association have only considered the perception of parents/caregivers [Viegas et al, 2012;Siqueira et al, 2013].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of study has involved primarily dental caries; there is a gap in the literature on the implications of malocclusion 5 and enamel defects on children's OHRQoL. Moreover, most studies have involved preschool children aged between 3 and 5 years of age 3,8,9 and there has been little research on younger children. Knowing that oral diseases, such as caries, are cumulative and tend to worsen with the increase in the age of the child, it is necessary to determine the occurrence of oral problems as early as possible to diminish the impact on children's quality of life.…”
Section: Introductionmentioning
confidence: 96%
“…Studies investigating the impact of malocclusion on the quality of life of preschool children have shown conflicting results. According to some cross-sectional studies, malocclusion is not associated with an adverse impact on the quality of life of preschool children and their families 5,8,9 . The apparent lack of sensitivity of available instruments to detect changes caused by malocclusion in the quality of life of preschool children may explain these results; however, other research conducted with children in southern Brazil revealed that malocclusion has a negative impact on a child's quality of life 7 .…”
Section: Introductionmentioning
confidence: 99%